Eutectic solvent electrolyte solution, preparation method thereof and aluminum ion secondary battery

By using non-AlCl3-based aluminum salts and hydrogen bond acceptor substances to prepare eutectic solvent electrolyte solutions, the high cost and corrosiveness problems of existing aluminum-ion battery electrolytes are solved, and the low-temperature performance and air stability of aluminum-ion secondary batteries are achieved. , improving the application potential of batteries.

CN114784384BActive Publication Date: 2025-01-21SHANGHAI JIAOTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202210393900.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-14
Publication Date
2025-01-21
Estimated Expiration
2042-04-14

AI Technical Summary

Technical Problem

The electrolytes of existing aluminum ion batteries such as AlCl3/[EMIm]Cl have high cost, corrosiveness, and sensitivity to air and water, which limits its application and commercialization process.

Method used

A eutectic solvent electrolyte solution is prepared using non-AlCl3-based aluminum salts and hydrogen bond acceptor substances. By controlling the molar ratio of aluminum salt and hydrogen bond acceptor, an electrolyte solution with low temperature performance and air stability is prepared.

Benefits of technology

It achieves the low-temperature performance and air stability of aluminum-ion secondary batteries, reduces production costs, avoids corrosive problems, and expands the application potential of batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114784384B_ABST
    Figure CN114784384B_ABST
Patent Text Reader

Abstract

The invention discloses a eutectic solvent electrolyte solution, a preparation method thereof and an aluminum ion secondary battery, and relates to the field of electrochemical energy storage technology. The eutectic solvent electrolyte solution is prepared by mixing an aluminum salt and a hydrogen bond acceptor substance, wherein the molar ratio of the aluminum salt and the hydrogen bond acceptor substance is 1:1-15; wherein the aluminum salt is selected from at least one of aluminum trifluoromethanesulfonate, aluminum nitrate, aluminum perchlorate and aluminum sulfate; and the hydrogen bond acceptor substance is selected from at least one of sulfone compounds and alcohol compounds. By screening the aluminum salt and the hydrogen bond acceptor substance and controlling the dosage of the two, the prepared electrolyte has good low temperature performance and air stability, and has great application potential in aluminum-based electrochemical energy storage devices.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a eutectic solvent electrolyte solution, a preparation method thereof and an aluminum ion secondary battery. Background Art

[0002] Aluminum ion batteries in multivalent metal ion battery systems are considered to be strong competitors in the field of new energy storage technologies. This is primarily because the abundance and safety of aluminum are expected to significantly improve the economy and safety of aluminum ion battery systems. In addition, aluminum can exchange three electrons in the electrochemical process and thus provide a volumetric capacity that is about four times that of lithium battery systems (Al: 8046 mAh cm -3 ). Therefore, aluminum-ion batteries are expected to be smaller in volume than lithium-ion batteries. The mass specific capacity of aluminum is 2980 mAh g -1 , second only to lithium (3860mAh g -1 ), which is higher than other metals (Na, K, Mg and Ca). Compared with other metal battery systems, although aluminum has a higher redox potential than other metals (-1.76V relative to the standard hydrogen electrode), the higher volume and weight specific capacity of the aluminum battery system will undoubtedly produce energy density close to or even higher. Therefore, aluminum-ion batteries are expected to be an important supplement to the current energy storage battery system due to their multiple advantages of low price, high safety and good comprehensive performance.

[0003] Aluminum metal, as a high theoretical energy carrier, has been in the field of vision since the 19th century in the form of Zn / H2SO4 / Al batteries. However, when aluminum comes into contact with air and most electrolytes, the dense surface film (Al2O3) hinders the electrochemical performance of Al metal. Unlike lithium metal, it is generally believed that the original oxide surface film on aluminum metal does not have ionic conductivity, that is, it cannot be used for Al 3+ Migration. In addition, Al 3+ Due to the high surface charge density, the chemical kinetics are slow. 3+ The standard electrode potential of Al (-1.68 V) is lower than that of H + / H2, Al electrodes cannot be charged in ordinary aqueous electrolytes. Therefore, in the early stages, due to various limitations of Al electrodes, they were only used in primary battery systems, such as Al / AgO, Al / H2O2 and Al / S batteries. In order to try secondary batteries with aluminum metal as anode, early researchers tried to use high-temperature molten salt electrolytes to ensure that the aluminum anode can achieve reversible deposition / stripping behavior, such as the NaCl-AlCl3 system, which is liquid and has high ionic conductivity at temperatures above 100°C. However, the harsh temperature requirements of the high-temperature molten salt and the disadvantages of more side reactions limit its application in rechargeable aluminum batteries. In 1985, researchers replaced high-temperature molten salts with ionic liquids to ensure that the reversible deposition / stripping behavior of Al can be carried out under room temperature conditions. Since then, ionic liquids based on AlCl3 / [EMIm]Cl have gradually been used as electrolytes for aluminum ion batteries. In 2015, Dai Hongjie's research group developed a secondary aluminum-ion battery consisting of a graphite foam positive electrode and an aluminum negative electrode based on AlCl3 / [EMIm]Cl ionic liquid electrolyte. It has the advantages of long cycle life, excellent rate performance and low cost. Since then, extensive research has been devoted to the development of secondary aluminum-ion batteries with stronger performance, among which a lot of work is mainly focused on the design and modification of positive electrode materials. It is well known that electrolyte, as a component of the battery, plays an important role in electrochemical energy storage devices and has a great influence on the electrochemical mechanism, which is no exception in aluminum-ion batteries. Therefore, finding a suitable electrolyte is crucial for aluminum-ion batteries.

[0004] So far, AlCl3 / [EMIm]Cl ionic liquid is the most commonly used electrolyte for aluminum ion batteries with aluminum as the negative electrode because it can achieve efficient reversible deposition / stripping of aluminum. However, the carrier ion in this ionic liquid is a monovalent compound AlCl 4- and Al2Cl 7- Instead of trivalent Al 3+ , which means that aluminum-ion batteries based on Al 3+ The value of the high theoretical capacity of the three electron transfer reactions cannot be fully realized, so the actual energy density of the related aluminum ion batteries is still unsatisfactory. In addition, AlCl3 / [EMIm]Cl ionic liquid has severe corrosiveness, and Al2Cl 7- and Cl -Ions can react with common metals such as aluminum, iron, nickel, titanium and tungsten. This feature not only shortens the service life of the Al negative electrode in aluminum-ion batteries, but also severely limits the selection of battery current collectors and shells. In addition, the high cost of AlCl3 / [EMIm]Cl ionic liquids and their excessive sensitivity to air and moisture have greatly hindered the commercialization of aluminum-ion batteries. Therefore, it is crucial to explore a new electrolyte that is air-stable, low-cost and non-corrosive for use in aluminum-ion batteries.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The object of the present invention is to provide a eutectic solvent electrolyte solution and a preparation method thereof, aiming to provide a non-AlCl3-based eutectic electrolyte that is economical, environmentally friendly, has low-temperature performance and air stability.

[0007] Another object of the present invention is to provide an aluminum ion secondary battery having excellent low temperature performance and air stability.

[0008] The present invention is achieved in that:

[0009] In a first aspect, the present invention provides a eutectic solvent electrolyte solution, comprising an aluminum salt and a hydrogen bond acceptor substance, wherein the molar ratio of the aluminum salt to the hydrogen bond acceptor substance is 1:1-15;

[0010] The aluminum salt is selected from at least one of aluminum trifluoromethanesulfonate, aluminum nitrate, aluminum perchlorate and aluminum sulfate; and the hydrogen bond acceptor substance is selected from at least one of sulfone compounds and alcohol compounds.

[0011] In an optional embodiment, the molar ratio of the aluminum salt to the hydrogen bond acceptor substance is 1:1-4.

[0012] In an optional embodiment, the molar ratio of the aluminum salt to the hydrogen bond acceptor substance is 1:1-2.

[0013] In an optional embodiment, the sulfone compound is selected from at least one of dimethyl sulfoxide and sulfolane.

[0014] In an optional embodiment, the alcohol compound is selected from at least one of ethylene glycol, polyethylene glycol-200, polyethylene glycol-400 and polyethylene glycol-600.

[0015] In a second aspect, the present invention provides a method for preparing the eutectic solvent electrolyte solution of any one of the aforementioned embodiments, comprising mixing an aluminum salt and a hydrogen bond acceptor substance.

[0016] In an optional embodiment, the aluminum salt and the hydrogen bond acceptor substance are heated at 40-60° C. for 30-60 min;

[0017] Preferably, after the heating is completed, the mixture is cooled to room temperature and stirred for 1-6 hours.

[0018] In a third aspect, the present invention provides an aluminum ion secondary battery, comprising a positive electrode material, a negative electrode material and the eutectic solvent electrolyte solution of any one of the aforementioned embodiments.

[0019] In an optional embodiment, the positive electrode material is selected from at least one of vanadium pentoxide, manganese dioxide, molybdenum disulfide, polyaniline, Prussian blue and graphite.

[0020] In an optional embodiment, the negative electrode material is selected from at least one of aluminum foil and Al-Mg-Sn alloy foil; preferably aluminum foil;

[0021] Preferably, the thickness of the negative electrode material is 1-300 μm.

[0022] The present invention has the following beneficial effects: a eutectic solvent electrolyte is prepared by using non-AlCl3-based aluminum salts and hydrogen bond acceptor substances as raw materials, and the aluminum salts and hydrogen bond acceptor substances are screened and their amounts are controlled, so that the prepared electrolyte has excellent low-temperature performance and air stability, and has great application potential in aluminum-based electrochemical energy storage devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 is the first cycle charge and discharge curve of the battery in Example 1;

[0025] Figure 2 This is the TOF-SIMs depth profile of the negative electrode aluminum foil after battery cycling in Example 1;

[0026] Figure 3 is the first cycle charge and discharge curve of the battery in Example 2;

[0027] Figure 4 This is a TOF-SIMs longitudinal cross-sectional image of the negative electrode aluminum foil after battery cycling in Example 2;

[0028] Figure 5 is the first cycle charge and discharge curve of the battery in Example 3;

[0029] Figure 6 This is a scanning electron microscope mapping image of the negative electrode aluminum foil after battery cycling in Example 3;

[0030] Figure 7 is the first cycle charge and discharge curve of the battery in Example 4;

[0031] Figure 8 This is a TOF-SIMs longitudinal cross-sectional image of the negative electrode aluminum foil after battery cycling in Example 4;

[0032] Fig. 9 is the first cycle charge and discharge curve of the battery in Example 5;

[0033] Fig.10 This is a TOF-SIMs 3D reconstructed image of the negative electrode aluminum foil after battery cycling in Example 5;

[0034] Fig.11 is the first cycle charge and discharge curve of the battery in Example 6;

[0035] Fig.12 This is a TOF-SIMs image of the surface layer of the negative electrode aluminum foil after battery cycling in Example 6;

[0036] Fig.13 is the first cycle charge and discharge curve of the battery in Example 7;

[0037] Fig.14 This is a TOF-SIMs 3D reconstructed image of the negative electrode aluminum foil after battery cycling in Example 7;

[0038] Fig.15 is the cycle performance of the battery in Example 8;

[0039] Fig.16 This is a TOF-SIMs longitudinal cross-sectional image of the negative electrode aluminum foil after battery cycling in Example 8;

[0040] Fig.17 Comparison of electrolyte air stability between Comparative Example 1 and Example 1;

[0041] Fig.18 Optical photos of the electrolytes of Comparative Example 2 and Example 1 at a low temperature of -70°C;

[0042] Fig.19 The figure is a comparison of the cycle performance of the batteries in comparative example 3 and example 1 at a low temperature of -70°C. DETAILED DESCRIPTION

[0043] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0044] Eutectic solvent is an ionic liquid analog with electrochemical properties similar to ionic liquids. It has attracted more and more attention in the battery field due to its low cost, easy preparation, green environmental protection, good chemical stability and other advantages. It is a mixture composed of hydrogen bond donors (polyols, urea and carboxylic acids) and hydrogen bond acceptors (quaternary ammonium salts, such as choline chloride, etc.). The most significant physical property is the reduction of the solvent melting point. Compared with traditional ionic liquids, the ions in the eutectic solvent form a loose cluster structure through hydrogen bonds. When it is used as an electrolyte for aluminum ion batteries, the related Al in the electrochemical process is 3+ The activation energy of complex dissociation is smaller, which can accelerate the kinetic process of aluminum ion batteries, so the eutectic solvent is very suitable for use as a low-temperature electrolyte for batteries.

[0045] The present invention provides a method for preparing a eutectic solvent electrolyte solution. An aluminum salt and a hydrogen bond acceptor substance are mixed to prepare the eutectic solvent electrolyte solution. The inventor selects raw materials for preparing the eutectic solvent electrolyte solution, adopts non-AlCl3-based aluminum salt and hydrogen bond acceptor substance as raw materials, and controls the dosage of the two, so that the prepared electrolyte has good low-temperature performance and air stability.

[0046] Specifically, the aluminum salt is selected from at least one of aluminum trifluoromethanesulfonate, aluminum nitrate, aluminum perchlorate and aluminum sulfate, and can be one or more; the hydrogen bond acceptor substance is selected from at least one of sulfone compounds and alcohol compounds, and can be a sulfone compound, an alcohol compound, or a mixture of a sulfone compound and an alcohol compound.

[0047] Further, the sulfone compound is selected from at least one of dimethyl sulfoxide and sulfolane; the alcohol compound is selected from at least one of ethylene glycol, polyethylene glycol-200, polyethylene glycol-400 and polyethylene glycol-600. The sulfone compound and the alcohol compound can be selected within the above range, and are both suitable for preparing a eutectic solvent electrolyte solution with the aluminum salt provided in the embodiment of the present invention.

[0048] Furthermore, the molar ratio of the aluminum salt to the hydrogen bond acceptor substance is 1: 1-15, preferably 1: 1-4, more preferably 1: 1-2. The low temperature performance and air stability of the electrolyte solution can be improved by further controlling the molar ratio of the aluminum salt to the hydrogen bond acceptor substance.

[0049] Specifically, the molar ratio of the aluminum salt to the hydrogen bond acceptor substance is 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10, 1:11, 1:12, 1:13, 1:14, 1:15, etc., and can also be any value between the above adjacent molar ratios.

[0050] In the actual preparation process, the aluminum salt and the hydrogen bond acceptor substance are mixed evenly, heated for a certain period of time, cooled to room temperature, and then stirred to obtain a clear and transparent electrolyte.

[0051] In some embodiments, the aluminum salt and the hydrogen bond acceptor substance are heated at 40-60° C. for 30-60 min, and the raw materials are mixed uniformly by heating. Specifically, the heating temperature can be 40° C., 45° C., 50° C., 55° C., 60° C., etc., or any value between the above adjacent temperature values. The heating time can be 30 min., 35 min., 40 min., 45 min., 50 min., 55 min., 60 min., etc., or any value between the above adjacent time values.

[0052] In some embodiments, after the heating is completed, the mixture is cooled to room temperature and stirred for 1-6 hours to obtain a clear and transparent electrolyte solution.

[0053] An embodiment of the present invention also provides a eutectic solvent electrolyte solution, which is prepared by the above-mentioned preparation method and has excellent low-temperature performance and air stability. The operating environment is -70 to 25°C. The mass change of the electrolyte solution in an air atmosphere is less than 20%, and liquid fluidity is maintained.

[0054] An embodiment of the present invention provides an aluminum ion secondary battery, comprising a positive electrode material, a negative electrode material and the above-mentioned eutectic solvent electrolyte solution. Through the improvement of the eutectic solvent electrolyte solution, the aluminum ion secondary battery has excellent low-temperature performance and air stability, and has great application potential in aluminum-based electrochemical energy storage devices.

[0055] In some embodiments, the positive electrode material is Al 3+ The storage material can realize aluminum ion intercalation, and specifically can be at least one of vanadium pentoxide, manganese dioxide, molybdenum disulfide, polyaniline, Prussian blue and graphite, and can be one or more.

[0056] In some embodiments, the negative electrode material is selected from at least one of aluminum foil and Al-Mg-Sn alloy foil; preferably aluminum foil; the thickness of the negative electrode material is 1-300 μm. When the negative electrode is aluminum foil, a solid electrolyte interface film (SEI film) composed of an Al-eutectic solvent complex is formed on the surface. The SEI film prevents the aluminum foil from being oxidized and causing passivation failure, and can inhibit the formation of aluminum dendrites during the deposition of aluminum in the eutectic solvent electrolyte.

[0057] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0058] Example 1

[0059] This embodiment provides a method for preparing a secondary aluminum ion battery, comprising the following steps:

[0060] (1) Preparation of electrolyte: Aluminum trifluoromethanesulfonate and hydrogen bond acceptor dimethyl sulfoxide were mixed in a molar ratio of 1:1, heated at 60°C for 60 min until the system was in a uniform liquid state, then naturally cooled to room temperature, and stirred for 3 h to obtain the corresponding eutectic solvent electrolyte.

[0061] (2) Battery assembly: The prepared eutectic electrolyte is used as the electrolyte of an aluminum ion battery, a pure aluminum foil (thickness 100 μm) is used as the negative electrode, and vanadium pentoxide is used as the positive electrode to assemble an aluminum ion battery.

[0062] After testing, the room temperature reversible discharge capacity of the battery prepared in this example is 300 mAh g -1 The reversible discharge capacity at low temperature of -70℃ is 271mAh g -1 , the charge and discharge curves are as follows Figure 1 As shown, TOF-SIMs depth analysis of the negative electrode aluminum foil after battery cycling is shown in Figure 2 As shown. Figure 2 It can be seen that the operating environment is -70 to 25°C, and the electrolyte solution maintains good performance in an air atmosphere.

[0063] Example 2

[0064] This embodiment provides a method for preparing a eutectic solvent electrolyte solution, comprising the following steps:

[0065] (1) Preparation of electrolyte: Aluminum nitrate and hydrogen bond acceptor ethylene glycol were mixed in a molar ratio of 1:4, heated at 50°C for 30 min until the system was in a uniform liquid state, then naturally cooled to room temperature, and stirred for 1 h to obtain the corresponding eutectic solvent electrolyte.

[0066] (2) Battery assembly: The prepared eutectic electrolyte is used as the electrolyte of an aluminum ion battery, an aluminum alloy foil is used as the negative electrode (thickness 10 μm), and manganese dioxide is used as the positive electrode to assemble an aluminum ion battery.

[0067] After testing, the reversible discharge capacity of the battery prepared in this example is 260 mAh g -1 The reversible discharge capacity at low temperature of -70℃ is 232mAh g -1 , the charge and discharge curves are as follows Figure 3 The TOF-SIMs longitudinal cross-sectional image of the negative electrode aluminum foil after battery cycling is shown in Figure 4 As shown, there is a SEI film with uniform thickness on the surface of the negative electrode aluminum foil, which inhibits the formation of aluminum dendrites and improves the coulombic efficiency and cycle stability of the battery. In addition, the low viscosity of the ligand ethylene glycol reduces the overall viscosity of the modified eutectic solvent electrolyte solution, so it has high ionic conductivity, which is beneficial to the electrochemical performance of the battery.

[0068] Example 3

[0069] This embodiment provides a method for preparing a eutectic solvent electrolyte solution, comprising the following steps:

[0070] (1) Preparation of electrolyte: Aluminum perchlorate and hydrogen bond acceptor cyclopentane sulfone were mixed in a molar ratio of 1:8, heated at 30°C for 60 min until the system was in a uniform liquid state, then naturally cooled to room temperature, and stirred for 6 h to obtain the corresponding eutectic solvent electrolyte.

[0071] (2) Battery assembly: The prepared eutectic electrolyte is used as the electrolyte of an aluminum ion battery, pure aluminum foil (300 μm thick) is used as the negative electrode, and molybdenum disulfide is used as the positive electrode to assemble an aluminum ion battery.

[0072] After testing, the room temperature reversible discharge capacity of the battery prepared in this example is 243 mAh g -1 , the reversible discharge capacity at low temperature of -70℃ is 222mAh g -1 The first cycle charge and discharge curve is as follows: Figure 5 The scanning electron microscope mapping image of the negative electrode aluminum foil after battery cycling is shown in Figure 6 As shown in the figure, the elements of the SEI film on the surface of the aluminum negative electrode are evenly distributed, and the electrostatic shielding effect of the surface cations makes the aluminum deposition more uniform, which improves the coulombic efficiency of the battery. In addition, the presence of hydrogen bond receptor sulfolane significantly increases the electrochemical stability window of the electrolyte, and the battery has excellent cycle stability.

[0073] Example 4

[0074] This embodiment provides a method for preparing a eutectic solvent electrolyte solution, comprising the following steps:

[0075] (1) Preparation of electrolyte: Aluminum sulfate and hydrogen bond acceptor polyethylene glycol-200 were mixed in a molar ratio of 1:12, heated at 40°C for 30 min until the system was in a uniform liquid state, then naturally cooled to room temperature, and stirred for 2 h to obtain a eutectic solvent electrolyte.

[0076] (2) Battery assembly: The prepared eutectic electrolyte was used as the electrolyte of an aluminum ion battery, pure aluminum foil (thickness 50 μm) was used as the negative electrode, and polyaniline was used as the positive electrode to assemble an aluminum ion battery.

[0077] After testing, the room temperature reversible discharge capacity of the battery prepared in this example is 249 mAh g -1 , the reversible discharge capacity at low temperature of -70℃ is 245mAh g -1 The first cycle charge and discharge curve is as follows: Figure 7 The TOF-SIMs longitudinal cross-sectional image of the negative electrode aluminum foil after battery cycling is shown in Figure 8As shown, the thickness of the SEI film on the surface of the aluminum negative electrode is uniform. The eutectic solvent electrolyte solution synthesized by aluminum sulfate and polyethylene glycol-200 has the properties of low viscosity and low freezing point, so the battery has excellent low temperature performance.

[0078] Example 5

[0079] This embodiment provides a method for preparing a eutectic solvent electrolyte solution, comprising the following steps:

[0080] (1) Preparation of electrolyte: Aluminum trifluoromethanesulfonate and hydrogen bond acceptor polyethylene glycol-400 were mixed in a molar ratio of 1:15, heated at 60°C for 35 min until the system was liquid, then naturally cooled to room temperature, and stirred for 3 h to obtain the corresponding eutectic solvent electrolyte.

[0081] (2) Battery assembly: The prepared eutectic electrolyte is used as the electrolyte of an aluminum ion battery, an aluminum alloy foil is used as the negative electrode, and Prussian blue is used as the positive electrode to assemble an aluminum ion battery.

[0082] After testing, the reversible discharge capacity of the battery prepared in this example is 168 mAh g -1 , low temperature -70℃ reversible discharge capacity is 120mAh g -1 The first cycle charge and discharge curve is as follows: Fig. 9 The TOF-SIMs 3D reconstruction image of the negative electrode aluminum foil after battery cycling is shown in Fig.10 As shown in the figure, the results show that there is a SEI film composed of ligand components on the surface of the aluminum negative electrode, which has the effect of inhibiting the formation of aluminum dendrites and improving the coulombic efficiency and cycle stability of the battery. And due to the presence of macromolecular organic aluminum salt (aluminum trifluoromethanesulfonate) in the component, Al in the electrolyte 3+ The desolvation energy is low, and the battery has good low-temperature and rate performance.

[0083] Example 6

[0084] This embodiment provides a method for preparing a eutectic solvent electrolyte solution, comprising the following steps:

[0085] (1) Preparation of electrolyte: Aluminum perchlorate, aluminum trifluoromethanesulfonate and hydrogen bond acceptor polyethylene glycol-400 were mixed in a molar ratio of 1:1:12, heated at 45°C for 35 min until the system was in a uniform liquid state, then naturally cooled to room temperature, and stirred for 3 h to obtain the corresponding eutectic solvent electrolyte.

[0086] (2) Battery assembly: The prepared eutectic electrolyte is used as the electrolyte of an aluminum ion battery, metallic aluminum is used as the negative electrode, and graphite is used as the positive electrode to assemble an aluminum ion battery.

[0087] After testing, the reversible discharge capacity of the battery prepared in this example is 250 mAh g -1, the reversible discharge capacity at low temperature of -70℃ is 220mAh g -1 The first cycle charge and discharge curve is as follows: Fig.11 The TOF-SIMs image of the surface of the negative electrode aluminum foil after battery cycling is shown in Fig.12 As shown, due to the ClO4 in the eutectic solvent electrolyte solution - and OTF - The co-participation of anions Al 3+ There is a uniform SEI film on the surface of the aluminum negative electrode, which can inhibit the formation of aluminum dendrites during charging and improve the coulombic efficiency and cycle stability of the battery. In addition, the low melting point of the three-component eutectic also gives the battery excellent low-temperature performance.

[0088] Example 7

[0089] This embodiment provides a method for preparing a eutectic solvent electrolyte solution, comprising the following steps:

[0090] (1) Preparation of electrolyte: Aluminum nitrate, aluminum sulfate, aluminum trifluoromethanesulfonate and dimethyl sulfoxide were mixed in a molar ratio of 0.3:0.1:0.6:15, heated at 40°C for 40 min until the system was in a uniform liquid state, then naturally cooled to room temperature, and stirred for 3 h to obtain the corresponding eutectic solvent electrolyte.

[0091] (2) Battery assembly: The prepared eutectic electrolyte is used as the electrolyte of an aluminum ion battery, metallic aluminum is used as the negative electrode, and polyaniline is used as the positive electrode to assemble an aluminum ion battery.

[0092] After testing, the reversible discharge capacity of the battery prepared in this example is 231 mAh g -1 , the reversible discharge capacity at low temperature of -70℃ is 225mAh g -1 The first cycle charge and discharge curve is as follows: Fig.13 The TOF-SIMs 3D reconstruction image of the negative electrode aluminum foil after battery cycling is shown in Fig.14 As shown in the figure, the SEI film on the surface of the aluminum negative electrode is uniform. Thanks to the stable and uniform SEI film, the battery exhibits high capacity and excellent cycle stability. In addition, the electrolyte is composed of a variety of aluminum salts and a variety of ligands, and the complexes in the electrolyte are diverse, giving the battery a higher capacity.

[0093] Example 8

[0094] This embodiment provides a method for preparing a eutectic solvent electrolyte solution, comprising the following steps:

[0095] (1) Preparation of electrolyte: Aluminum nitrate, aluminum sulfate, aluminum perchlorate, aluminum trifluoromethanesulfonate and hydrogen bond acceptor thiourea (containing C=S) were mixed in a molar ratio of 0.3:0.1:0.3:0.3:10, heated at 50°C for 30 min until the system was in a uniform liquid state, then naturally cooled to room temperature, and stirred for 2 h to obtain the corresponding eutectic solvent electrolyte.

[0096] (2) Battery assembly: The prepared eutectic electrolyte is used as the electrolyte of an aluminum ion battery, metallic aluminum is used as the negative electrode, and molybdenum disulfide is used as the positive electrode to assemble an aluminum ion battery.

[0097] After testing, the reversible discharge capacity of the battery prepared in this embodiment is 350mAh g-1 at room temperature, 298mAh g-1 at low temperature of -70℃, and the cycle performance is as follows: Fig.15 The TOF-SIMs longitudinal cross-sectional image of the negative electrode aluminum foil after battery cycling is shown in Fig.16 As shown in the figure, the presence of multiple anions in the electrolyte contributes to the uniform formation of the SEI film, which inhibits the formation of aluminum dendrites and improves the coulombic efficiency and cycle stability of the battery. In addition, the multi-component eutectic exhibits a lower freezing point, which is beneficial to the low-temperature performance of the battery. And the diverse solvation structure of the electrolyte is also beneficial to the rate performance and stability of the battery.

[0098] Example 9

[0099] This embodiment provides a method for preparing a secondary aluminum ion battery, comprising the following steps:

[0100] (1) Preparation of electrolyte: Aluminum trifluoromethanesulfonate and hydrogen bond acceptor dimethyl sulfoxide were mixed in a molar ratio of 1:2, heated at 60°C for 60 min until the system was in a uniform liquid state, then naturally cooled to room temperature, and stirred for 3 h to obtain the corresponding eutectic solvent electrolyte.

[0101] (2) Battery assembly: The prepared eutectic electrolyte is used as the electrolyte of an aluminum ion battery, a pure aluminum foil (thickness 100 μm) is used as the negative electrode, and vanadium pentoxide is used as the positive electrode to assemble an aluminum ion battery.

[0102] The only difference from Example 1 is that the molar ratio of aluminum to hydrogen bond acceptor is 1:2.

[0103] After testing, the room temperature reversible discharge capacity of the battery prepared in this example is 330 mAh g -1 , the reversible discharge capacity at low temperature of -70℃ is 270mAh g -1 .

[0104] Example 10

[0105] The only difference from Example 1 is that the molar ratio of aluminum to hydrogen bond acceptor is 1:4.

[0106] After testing, the room temperature reversible discharge capacity of the battery prepared in this example is 290 mAh g -1 , the reversible discharge capacity at low temperature of -70℃ is 255mAh g -1 .

[0107] Embodiment 11

[0108] The only difference from Example 1 is that the molar ratio of aluminum to hydrogen bond acceptor is 1:6.

[0109] After testing, the room temperature reversible discharge capacity of the battery prepared in this example is 275 mAh g -1 , the reversible discharge capacity at low temperature of -70℃ is 245mAh g -1 .

[0110] Example 12

[0111] The only difference from Example 1 is that the molar ratio of aluminum to hydrogen bond acceptor is 1:8.

[0112] After testing, the reversible discharge capacity of the battery prepared in this example is 263 mAh g -1 The reversible discharge capacity at low temperature of -70℃ is 233mAh g -1 .

[0113] Embodiment 13

[0114] The only difference from Example 1 is that the molar ratio of aluminum to hydrogen bond acceptor is 1:10.

[0115] After testing, the reversible discharge capacity of the battery prepared in this example is 250 mAh g -1 , the reversible discharge capacity at low temperature of -70℃ is 222mAh g -1 .

[0116] Embodiment 14

[0117] The only difference from Example 1 is that the molar ratio of aluminum to hydrogen bond acceptor is 1:12.

[0118] After testing, the room temperature reversible discharge capacity of the battery prepared in this example is 241 mAh g -1 , low temperature -70℃ reversible discharge capacity 215mAh g -1 .

[0119] Comparative Example 1

[0120] The eutectic solvent electrolyte was prepared in the same manner as in Example 1, except that the type of aluminum salt was AlCl 3. The other steps were the same as in Example 1, and an aluminum secondary battery was prepared.

[0121] Fig.17 The stability test is conducted by exposing the electrolytes of Comparative Example 1 and Example 1 to air environment conditions. It can be seen that the electrolyte of Comparative Example 1 loses its liquid fluidity in the air; in contrast, the electrolyte of Example 1 still maintains its initial low viscosity and liquid fluidity, indicating that the non-AlCl3-based eutectic solvent electrolyte has excellent air stability.

[0122] Comparative Example 2

[0123] A eutectic solvent electrolyte was prepared in the same manner as in Example 1, except that 50% by mass of water was added to the eutectic electrolyte. The other steps were the same as in Example 1, and an aluminum secondary battery was prepared.

[0124] Fig.18 Optical photos of the electrolytes in Comparative Example 2 and Example 1 at low temperature -70°C. It can be seen that the electrolyte in Comparative Example 2 is solid at low temperature -70°C; in contrast, the electrolyte in Example 1 remains in a clear and transparent liquid state. This indicates that adding water to the eutectic solvent electrolyte will transform the electrolyte into an aqueous solution, thus losing the property of a low freezing point.

[0125] Comparative Example 3

[0126] The eutectic solvent electrolyte was prepared in the same manner as in Example 1, except that the ligand was an amide compound, thioacetamide. The other steps were the same as in Example 1, and an aluminum secondary battery was prepared.

[0127] Fig.19 The cycling performance of the battery in comparative example 3 and example 1 is compared. It can be seen that the discharge capacity of the battery in comparative example 3 decays rapidly at a low temperature of -70 degrees Celsius, and the initial discharge capacity decreases from 170 mAh g -1 After 100 cycles, it becomes 25 mAh g -1 In contrast, the battery in Example 1 has excellent low-temperature cycle performance, with an initial discharge capacity of 271 mAh g -1 After 100 cycles, it can still maintain a stable 250mAh g -1 . This shows that for eutectic solvent electrolytes, liquid hydrogen bond acceptor components can make the battery have better low-temperature performance than solid hydrogen bond acceptor components.

[0128] Comparative Example 4

[0129] The only difference from Example 1 is that the molar ratio of aluminum to hydrogen bond acceptor is 1:0.5.

[0130] After testing, the reversible discharge capacity of the battery prepared in this example is 150 mAh g -1 , the reversible discharge capacity at low temperature of -70℃ is 80mAh g-1 .

[0131] Comparative Example 5

[0132] The only difference from Example 1 is that the molar ratio of aluminum to hydrogen bond acceptor is 1:20.

[0133] After testing, the reversible discharge capacity of the battery prepared in this example is 170 mAh g -1 , low temperature -70℃ reversible discharge capacity is 100mAh g -1 .

[0134] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A eutectic solvent electrolyte solution, characterized in that: It comprises an aluminum salt and a hydrogen bond acceptor substance, wherein the molar ratio of the aluminum salt to the hydrogen bond acceptor substance is 1:1-15; Wherein, the aluminum salt is selected from at least one of aluminum trifluoromethanesulfonate, aluminum nitrate, aluminum perchlorate and aluminum sulfate; the hydrogen bond acceptor substance is selected from at least one of sulfone compounds and alcohol compounds; The sulfone compound is selected from at least one of dimethyl sulfoxide and sulfolane; The alcohol compound is selected from at least one of ethylene glycol, polyethylene glycol-200, polyethylene glycol-400 and polyethylene glycol-600.

2. The eutectic solvent electrolyte solution according to claim 1, characterized in that The molar ratio of the aluminum salt to the hydrogen bond acceptor substance is 1:1-4.

3. The eutectic solvent electrolyte solution according to claim 2, characterized in that The molar ratio of the aluminum salt to the hydrogen bond acceptor substance is 1:1-2.

4. The method for preparing the eutectic solvent electrolyte solution according to any one of claims 1 to 3, characterized in that: The aluminum salt and the hydrogen bond acceptor substance are mixed, and the aluminum salt and the hydrogen bond acceptor substance are heated at 40-60° C. for 30-60 minutes.

5. The preparation method according to claim 4, characterized in that: After heating is complete, cool to room temperature and stir for 1-6 h.

6. An aluminum ion secondary battery, characterized in that: The invention comprises a positive electrode material, a negative electrode material and the eutectic solvent electrolyte solution according to any one of claims 1 to 3.

7. The aluminum ion secondary battery according to claim 6, characterized in that: The positive electrode material is selected from at least one of vanadium pentoxide, manganese dioxide, molybdenum disulfide, polyaniline, Prussian blue and graphite.

8. The aluminum ion secondary battery according to claim 6, characterized in that: The negative electrode material is selected from at least one of aluminum foil and Al-Mg-Sn alloy foil.

9. The aluminum ion secondary battery according to claim 8, characterized in that: The negative electrode material is aluminum foil.

10. The aluminum ion secondary battery according to claim 8, characterized in that: The thickness of the negative electrode material is 1-300 μm.

Citation Information

Patent Citations

  • Low-cost aluminum-based electrolyte and aluminum battery application thereof

    CN109713369A

  • Ionic liquid-like electrolyte for aluminum secondary battery and preparation method of ionic liquid-like electrolyte

    CN113097565A